Messiah : the composition and afterlife of Handel's masterpiece - Keates, Jonathan, 1946- (New York : Basic Books, 2017)
"In the late summer of 1741, George Friderick Handel composed an oratorio set to words from the King James Bible, rich in tuneful arias and magnificent choruses. Jonathan Keates recounts the history and afterlife of Messiah, one of the best-loved works in the classical repertoire. He relates the composition's first performances and its relationship with spirituality in the age of the Enlightenment, and examines how Messiah, after Handel's death, became an essential component of our musical canon. An authoritative and affectionate celebration of the high-point of the Georgian golden age of music, Messiah is essential reading for lovers of classical music." -- Publisher's description
A composer at the crossroads -- The world of oratorio -- To the Hibernian shore -- Elevated, majestic and moving -- The mysterious Mr Jennens -- The Lord gave the word -- Composing Messiah -- A work in progress -- Finding an audience -- Blessing & honour & glory & power -- Appendix I. Libretto of Messiah -- Appendix II. Jennens's scenic structure for Messiah -- Appendix III. Timeline of the life and times of George Frideric Handel.
Includes bibliographical references (pages 153-160) and index.
Keywords: Handel, George Frideric, -- 1685-1759.; Oratorio; HISTORY / Europe / Germany; HISTORY / Europe / Great Britain; MUSIC / Genres & Styles / Classical; MUSIC / Genres & Styles / Opera; MUSIC / History & Criticism; MUSIC / Individual Composer & Musician; MUSIC / Religious / Christian